Pemerolehan Kata Anak Usia Lima Tahun Melalui Penceritaan Dongeng di TK Aisyiyah Pilang Masaran Sragen - Rohman, Arifin Ainur; , Prof. Dr. Harun Joko Prayitno, M.Hum; , Dra. Atiqa Sabardila, M. Hum (2015)
The purpose of the reseach (1) Describe the acquisition of the various words of children aged five years as he recounted a tale heard (2) Describe the class acquisition five years old boy said as he recounted a tale heard. This study used a qualitative descriptive method. Data collection techniques using interview techniques, recording, and record. Test the validity of the source data using triangulation techniques. Analysis of data using a unified method. Results of the study showed that the acquisition of words on each child is different between one another. acquisition of said child already covers almost the entire class of existing words. Of the ten classes of existing words, most of the child's vocabulary already include nouns, verbs, adjectives, adverbs, pronouns, numeralia, prepositions, and. conjunctions. Noun word class occupies the highest position held by a child. It is inversely proportional to the class Interjection words that are not found at all in the speech of children studied.